2011
DOI: 10.1038/jhg.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

SLC2A1 gene analysis of Japanese patients with glucose transporter 1 deficiency syndrome

Abstract: Glucose transporter 1 deficiency syndrome (Glut1-DS) is a congenital metabolic disorder characterized by refractory seizures with early infantile onset, developmental delay, movement disorders and acquired microcephaly. Glut1-DS is caused by heterozygous abnormalities of the SLC2A1 (Glut1) gene, whose product acts to transport glucose into the brain across the blood-brain barrier. We analyzed the SLC2A1 gene in 12 Japanese Glut1-DS patients who were diagnosed by characteristic clinical symptoms and hypoglycorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
19
0
3
Order By: Relevance
“…Since we reported the first case of GLUT-1DS in Japan in 2004, the number of cases has gradually accumulated [18,20,24]. This study is a first nation-wide The total number of patient showing focal and generalized epileptiform discharges exceeded those having epileptiform EEG discharges because some patients had both focal and generalized EEG discharges.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Since we reported the first case of GLUT-1DS in Japan in 2004, the number of cases has gradually accumulated [18,20,24]. This study is a first nation-wide The total number of patient showing focal and generalized epileptiform discharges exceeded those having epileptiform EEG discharges because some patients had both focal and generalized EEG discharges.…”
Section: Discussionmentioning
confidence: 90%
“…Familial cases with autosomal dominant and recessive transmission have recently been described and included a parent or siblings having the same SLC2A1 mutation to a proband who exhibited the typical clinical characteristics, but almost no clinical symptoms or mild symptoms [9,20,30,32]. Hashimoto et al already reported the details of the two families included in the present study, in which both families included an affected parent and sibling and mild clinical symptoms in the mother were undiagnosed until the proband was diagnosed [20].…”
Section: Missense Mutationmentioning
confidence: 82%
See 3 more Smart Citations